2000
DOI: 10.1128/jb.182.1.23-29.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SoxS-Regulated Genes in Salmonella enterica Serovar Typhimurium

Abstract: Salmonella enterica serovar Typhimurium responds to superoxide-generating agents through soxR-mediated activation of the soxS gene, whose product, SoxS, is necessary for resistance to oxidative stress. The S. enterica serovar Typhimurium soxRS system also mediates redox-inducible resistance to diverse antibiotics, which may be relevant to clinical infections. In order to identify SoxS-regulated genes in S. enterica serovar Typhimurium, a lacI-regulated expression system for the S. enterica serovar Typhimurium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 35 publications
(28 reference statements)
2
81
0
1
Order By: Relevance
“…OmpF expression was decreased in 104-cip, consistent with the role of marRAB and soxRS in the control of its expression (37,40). This mutant also displayed alterations in the LPS ladder.…”
Section: Discussionmentioning
confidence: 54%
“…OmpF expression was decreased in 104-cip, consistent with the role of marRAB and soxRS in the control of its expression (37,40). This mutant also displayed alterations in the LPS ladder.…”
Section: Discussionmentioning
confidence: 54%
“…As in E. coli, increased expression of marA and soxS results in the Mar phenotype [11,31,59]. Recently, Koutsolioutsou et al [31] reported a soxRS-constitutive mutation in a clinical strain of S. enterica serovar Typhimurium that arose with the development of resistance to quinolones during treatment.…”
Section: Active Effluxmentioning
confidence: 99%
“…The marRAB and soxRS operons also occur in Salmonella [11,31,33,58,59,67]. As in E. coli, increased expression of marA and soxS results in the Mar phenotype [11,31,59].…”
Section: Active Effluxmentioning
confidence: 99%
“…Ten candidates were identified from ∼10,000 mutants screened. Insertion locations were determined by amplifying and sequencing adjacent genomic DNA as described previously (48).…”
Section: Methodsmentioning
confidence: 99%